1999
DOI: 10.1091/mbc.10.4.1077
|View full text |Cite
|
Sign up to set email alerts
|

The Yck2 Yeast Casein Kinase 1 Isoform Shows Cell Cycle-specific Localization to Sites of Polarized Growth and Is Required for Proper Septin Organization

Abstract: Casein kinase 1 protein kinases are ubiquitous and abundant Ser/Thr-specific protein kinases with activity on acidic substrates. In yeast, the products of the redundant YCK1 andYCK2 genes are together essential for cell viability. Mutants deficient for these proteins display defects in cellular morphogenesis, cytokinesis, and endocytosis. Yck1p and Yck2p are peripheral plasma membrane proteins, and we report here that the localization of Yck2p within the membrane is dynamic through the cell cycle. Using a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 86 publications
(122 reference statements)
5
72
0
Order By: Relevance
“…2C). In addition, CK1␦ has been localized to the Golgi, vesicular transporting vesicles, and plasma membrane in yeast and mammalian cells (24,(43)(44)(45)(46), consistent with the idea of CK1␦-mediated phosphorylation occurring during Cx43 connexon trafficking or after arrival at the plasma membrane. Wherever CK1 phosphorylation occurs, our cell surface biotinylation results indicate that the consequences of CK1 inhibition appear to be an accumulation of non-junctional Cx43 in the plasma membrane (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…2C). In addition, CK1␦ has been localized to the Golgi, vesicular transporting vesicles, and plasma membrane in yeast and mammalian cells (24,(43)(44)(45)(46), consistent with the idea of CK1␦-mediated phosphorylation occurring during Cx43 connexon trafficking or after arrival at the plasma membrane. Wherever CK1 phosphorylation occurs, our cell surface biotinylation results indicate that the consequences of CK1 inhibition appear to be an accumulation of non-junctional Cx43 in the plasma membrane (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…We previously reported that Yck2p is differentially enriched at sites of polarized secretion during the cell cycle (Robinson et al, 1999). The localization pattern we observed resembles that of proteins directed to the plasma membrane via the classical secretory pathway.…”
supporting
confidence: 58%
“…Actin was localized normally in Abnormal septin filaments do not contain Gin4. All bud neck proteins so far tested except for casein kinase (Robinson et al, 1999) were localized at the bud neck in a septin-dependent manner (Gladfelter et al, 2001). To examine whether the localization of a bud neck protein whose localization is dependent on septin is affected by FCF, we examined Gin4, which is a Nim1-related kinase that is localized at the bud neck in a septin-dependent manner .…”
Section: Resultsmentioning
confidence: 99%
“…Some mutations are known to cause changes in the morphology of septin filaments: ∆ gin4 , yck2 ts (Robinson et al, 1999), ∆ cla4 (Cvrckowa et al, 1995;Weiss et al, 2000), ∆ ste20 (Cvrckowa et al, 1995), ∆ bni5 (Lee et al, 2002), and elm1 (Bouquin et al, 2000) are among such mutations and they may be in factors affecting septin dynamics. Versele and Thorner (2004) showed the involvement of phosphorylation of Cdc10 by Cla4 in septin filament formation at the bud neck.…”
Section: Introductionmentioning
confidence: 99%